Impacts of PM2.5 Chemical Composition on Aerosol Light Extinction During the Xi’an International Horticultural Expo of China - Wang, Qiyuan; Zhou, Yaqing; Liu, Suixin; Zhang, Ting; Tian, Jie (Journal of Environmental Science and Engineering Technology, 2020)
In this study, we investigated the impacts of PM2.5 chemical composition on aerosol light extinction during the Xi’an International Horticultural Expo of China. The average mass concentration of PM2.5 was 118.1 ± 57.3 µg m-3 during the entire campaign with 23.1% and 40.7% contributed by carbonaceous aerosols and water-soluble inorganic ions. The average light extinction was 957.7 ± 643.5 Mm-1, of which >90% was contributed by the particle light scattering. The light extinction was 1.6 times larger during polluted period than the unpolluted period. The diurnal pattern of the measured light scattering was associated with the anthropogenic activities of daily life and the daily variation of boundary-layer height. Based on the IMPROVE equation, (NH4)2SO4 was the largest contributor to light extinction (35.3%) during the Xi’an International Horticultural Expo, followed by organic matter (33.7%), NH4NO3 (20.5%), EC (6.3%), and fine soil (4.0%). The light extinction produced by (NH4)2SO4, organic matter, and NH4NO3 were 1.8 – 2.5 times larger during polluted period than the unpolluted period. The results indicated that (NH4)2SO4 was the most important chemical composition in PM2.5 affecting the aerosol light extinction during the Xi’an International Horticultural Expo.